The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1093/hmg/ddx382
|View full text |Cite
|
Sign up to set email alerts
|

Modeling neuro-immune interactions during Zika virus infection

Abstract: Although Zika virus (ZIKV) infection is often asymptomatic, in some cases, it can lead to birth defects in newborns or serious neurologic complications in adults. However, little is known about the interplay between immune and neural cells that could contribute to the ZIKV pathology. To understand the mechanisms at play during infection and the antiviral immune response, we focused on neural precursor cells (NPCs)-microglia interactions. Our data indicate that human microglia infected with the current circulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 62 publications
4
36
0
1
Order By: Relevance
“…We note that pMGLs, in contrast to NPCs, can still mount a response to the virus: in certain circumstances they may help limit viral spread in the CNS parenchyma, for example, at later stages when more mature and present at higher density. A study published while this manuscript was under review (43), supporting many of our own findings, suggest this may indeed be the case: cocultures of NPCs and iPS-derived macrophages demonstrated less viral positivity than NPCs alone after exposure to ZIKV. The authors concluded there was active removal of infected NPCs by macrophages, highlighting the complex interplay between their role as vectors and as protective actors.…”
Section: Discussionsupporting
confidence: 78%
“…We note that pMGLs, in contrast to NPCs, can still mount a response to the virus: in certain circumstances they may help limit viral spread in the CNS parenchyma, for example, at later stages when more mature and present at higher density. A study published while this manuscript was under review (43), supporting many of our own findings, suggest this may indeed be the case: cocultures of NPCs and iPS-derived macrophages demonstrated less viral positivity than NPCs alone after exposure to ZIKV. The authors concluded there was active removal of infected NPCs by macrophages, highlighting the complex interplay between their role as vectors and as protective actors.…”
Section: Discussionsupporting
confidence: 78%
“…42 Further, microglia have been found to devour ZIKV-infected NPCs and to transmit the virus to uninfected NPCs. 43 This is consistent with the previously mentioned Trojan horse mechanism.…”
Section: Glial Cellssupporting
confidence: 91%
“…During human fetal brain development, as neurons and glia emerge from NPs, or as microglia migrate into the brain, these cell types are susceptible to ZIKV infection. Evidence suggests that neuronal function can be impaired by ZIKV (40), and glial cells that are less acutely impacted could serve as viral reservoirs (8,41). In the current study, we investigated whether ZIKV host factors in NPs also mediate infection of astrocytes.…”
Section: Discussionmentioning
confidence: 97%